EVALUASI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KOTA SUKABUMI - Dapit Saleh (Jurnal Inovasi Penelitian, 2021)
This research is entitled Evaluation of the city without slums (KOTAKU) program in Sukabumi City. This study aims to evaluate the slum-free city program in Sukabumi City by knowing the obstacles and efforts made by the government to deal with slum areas in Sukabumi City. The method used in this study is a qualitative descriptive method with data collection techniques through observation, interviews and documentation. This study uses six policy evaluation indicators from Dunn (2003). This research was conducted at the Department of Public Works, Spatial Planning, Housing, Settlement Areas and Land. The results of this study indicate that the implementation of the city program has not run optimally. There are still many slum areas that have not been handled. The handling of slum areas is carried out in a priority and gradual manner so that it takes a long time. Lack of prevention of slum areas that have been handled so that they do not return to slums. Lack of public awareness and concern in protecting the environment. And there are still many people who live on the edge of the train, the river whose ownership is not clear so it is not handled. .